2004
DOI: 10.1097/00126334-200401010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Marijuana Use Among Patients With HIV/AIDS Followed in a Public Health Care Setting

Abstract: The findings suggest that providers be advised to assess routinely and better understand patients' "indications" for self-administration of cannabis. Given the estimated prevalence, more formal characterization of the patterns and impact of cannabis use to alleviate HIV-associated symptoms is warranted. Clinical trials of smoked and noncombustible marijuana are needed to determine the role of cannabinoids as a class of agents with potential to improve quality of life and health care outcomes among patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
102
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 30 publications
7
102
2
Order By: Relevance
“…Surprisingly, this controversy is still unsettled. Indeed, although clinical trials of cannabis in affective disorders have yielded mixed results (7,8), many patients continue to report benefits from its use in primary or secondary depressive syndromes (9)(10)(11)(12)(13). One likely explanation for these contrasting data is suggested by the diversity of functions served by CB 1 receptors in the brain (14), which makes it difficult to separate the mood-elevating actions of ⌬ 9 -THC from its unwanted psychotropic effects.…”
mentioning
confidence: 99%
“…Surprisingly, this controversy is still unsettled. Indeed, although clinical trials of cannabis in affective disorders have yielded mixed results (7,8), many patients continue to report benefits from its use in primary or secondary depressive syndromes (9)(10)(11)(12)(13). One likely explanation for these contrasting data is suggested by the diversity of functions served by CB 1 receptors in the brain (14), which makes it difficult to separate the mood-elevating actions of ⌬ 9 -THC from its unwanted psychotropic effects.…”
mentioning
confidence: 99%
“…However, in our sample, smokers were less likely to use crack but and more likely to smoke marijuana. Although marijuana smoking for medicinal purposes remains controversial, evidence suggests that some HIV+ individuals believe that marijuana relieves some HIVrelated symptoms (Prentiss et al, 2004).Results also demonstrated an association between psychosocial factors and smoking. The odds of heavy smoking increased with lower levels of perceived social support.…”
mentioning
confidence: 77%
“…Marijuana use, in particular, is used at a high rate for recreational and medicinal purposes (Furler et al, 2004;Prentiss, Power, Balmas, Tzuang, & Israelski, 2004). Evidence linking any drug use and smoking in this population is mixed, with some research finding no relationship (Gritz et al, 2004) and others finding a positive relationship (Burkhalter et al, 2005).…”
Section: High Smoking Prevalence Among Hiv+ Men and Women: Examining mentioning
confidence: 99%
See 1 more Smart Citation
“…Only f e w o f t h e m ( 9 . 1 % ) r e p o r t e d s m o k i n g marijuana/using dronabinol ineffective (Prentiss et al, 2004). Moreover, Haney et al showed also that cannabinoids from marijuana or dronabinol can improve mood without producing disruptions in psychomotor functioning and add benefit of improving rating of sleep (Haney et al, 2007).…”
Section: Mood Controlmentioning
confidence: 99%